Маша и медведь: [для детей дошкольного возраста] / художник В. А. Жигарев - Жигарев В. А. (Фламинго, 2015)
Экземпляры: дб (20151119) / Инвентарный номер: 41063 / Цена: 44.00 / Авт.знак: М 38 / ГРНТИ: 17.82.93 / ББК: 84 (2Рос=Рус)6